The Influence of Motivation and Leadership Style on Productivity and Performance of Education Management in Aliyah Madrasah Swasta (MAS) AS'AD Jambi City - A Khalik; A A. Musyaffa; Hapzi Ali (International Journal of Supply Chain Management, 2020)
The current research emphasized on the teacher’s performance in supply chain perspective influenced by education suppliers, supply chain education and leadership styles among educational staff in Madrasah Aliyah Private (MAS) As'ad Jambi City. The population in this study is the teacher at MAS As'ad Jambi City as many as 38 teachers. The approach in this study uses a quantitative approach to the survey method and utilized SAMRT-PLS for analysis. The study reported that education suppliers, supply chain education and leadership styles influence the teachers’ performance that is required for effective supply chain management.